Saccharomyces cerevisiae morphology under hyperbaric gases - Coelho, M. A. Z. (2007)
The effects of hyperbaric stress on the morphology of Saccharomyces cerevisiae were studied in batch cultures under pressures between 0.1 MPa and 0.6 MPa and different gas compositions (air, O2, N2, or CO2), covering aerobic and anaerobic conditions. A method using automatic image analysis for cell classification based on their morphology was applied to experimental data. Cell viability was assessed through the Methylene Blue staining method and the percentages of viable and non-viable cells were also estimated using digital image processing. The results show that the effect of pressure on cell activity strongly depends on the nature of the gas used for pressurization. While nitrogen and air to a maximum of 0.6 MPa of pressure were innocuous to yeast, oxygen and carbon dioxide pressure caused cell inactivation, which was confirmed by the reduction on the number of budding cells with time and also a decrease in the average cell size (0.6 MPa CO2). A model taking into account cell viability reveals the opposing effects between oxygen availability and the baric and oxidative stresses present on the system. It is shown that cell viability in general is not constant during the experiments but strongly depends on the environment.